Cervical CT scan-guided epidural blood patches for spontaneous intracranial hypotension. Issue 12 (December 2015) - Maingard, Julian; Giles, Lauren; Marriott, Mark; Phal, Pramit M.
Highlights: Spontaneous intracranial hypotension (SIH) is an important differential in new daily postural headache. The utilisation of varying imaging modalities may be necessary to confirm a diagnosis of SIH. CT-guided cervical epidural blood patching (EBP) is an effective technique in the management of patients with refractory SIH. Abstract: We describe two patients with spontaneous intracranial hypotension (SIH), presenting with postural headache due to C1–C2 cerebrospinal fluid (CSF) leak. Both patients were refractory to lumbar epidural blood patching (EBP), and subsequently underwent successful CT scan-guided cervical EBP. SIH affects approximately 1 in 50, 000 patients, with females more frequently affected. Its associated features are variable, and as such, misdiagnosis is common. Therefore, imaging plays an important role in the diagnostic workup of SIH and can include MRI of the brain and spine, CT myelogram, and radionuclide cisternography. In patients with an established diagnosis and confirmed CSF leak, symptoms will usually resolve with conservative management. However, in a select subgroup of patients, the symptoms are refractory to medical management and require more invasive therapies. In patients with cervical leaks, EBP in the cervical region is an effective management approach, either in close proximity to, or directly targeting a dural defect. CT scan-guided cervical EBP is an effective treatment approach in refractory SIH, and should be considered in those patients who are refractory to conservative management.